Southern Argentina Agile Meteor Radar: System design and initial measurements of large-scale winds and tides - Fritts, D.C. (2010)
The Southern Argentina Agile Meteor Radar (SAAMER) was installed at Rio Grande on Tierra del Fuego (53.8°S, 67.8°W) in May 2008 and has been operational for ∼24 months. This paper describes the motivations for the radar design and its placement at the southern tip of South America, its operating modes and capabilities, and observations of the mean winds, planetary waves, and tides during its first ∼20 months of operation. SAAMER was specifically designed to provide very high resolution of large-scale motions and hopefully enable direct measurements of the vertical momentum flux by gravity waves, which have only been possible previously with dual- or multiple-beam radars and lidars or in situ measurements. SAAMER was placed on Tierra del Fuego because it was a region devoid of similar measurements, the latitude was anticipated to provide high sensitivity to an expected large semidiurnal tide, and the region is now recognized to be a "hot spot" of small-scale gravity wave activity extending from the troposphere into the mesosphere and lower thermosphere, perhaps the most dynamically active location on Earth. SAAMER was also intended to permit simultaneous enhanced meteor studies, including "head echo" and "nonspecular" measurements, which were previously possible only with high-power large-aperture radars. Initial measurements have defined the mean circulation and structure, exhibited planetary waves at various periods, and revealed large semidiurnal tide amplitudes and variability, with maximum amplitudes at higher altitudes often exceeding 60 m s-1 and amplitude modulations at periods from a few to ∼30 days.